Multinationals, technology transfer and domestic R&D incentives - Campos, Jaime F. (2007)
This thesis is a collection of four essays which aim to make a contribution to the theoretical analysis of the impact that flows of FDI have on fast growing developing countries, in which foreign firms not only invest but also set up R&D facilities. More precisely, we study these issues in a context in which both the mode of foreign expansion and the incentives to innovate are endogenously determined.